2013
DOI: 10.1002/ajmg.a.35632
|View full text |Cite
|
Sign up to set email alerts
|

Complex craniosynostosis is associated with the 2p15p16.1 microdeletion syndrome

Abstract: In a screening project of patients with (complex) craniosynostosis using genomic arrays, we identified two patients with craniosynostosis and microcephaly with a deletion in the 2p15p16.1 chromosomal region. This region has been associated with a new microdeletion syndrome, for which patients have various features in common, including microcephaly and intellectual disability. Deletions were identified using Affymetrix 250K SNP array and further characterized by fluorescence in situ hybridization (FISH) analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 28 publications
(51 reference statements)
0
24
0
Order By: Relevance
“…Following the initial report in 2007 by Rajcan-Separovic et al [Rajcan-Separovic et al, 2007], there have been 15 patients reported in the literature with overlapping deletions in this region [Chabchoub et al, 2008;Fannemel and Barøy, 2014;Florisson et al, 2013;Félix and Petrin, 2010;Hancarova et al, 2013;Hucthagowder et al, 2012;Liang et al, 2009;Peter et al, 2014;Piccione et al, 2012;Prontera et al, 2011;de Leeuw et al, 2008], in addition to reports from public databases such as DECIPHER and ISCA [Firth et al, 2009;Miller et al, 2010] and other large studies assessing developmental delay and copy number variants [Cooper et al, 2011;Kaminsky et al, 2011]. All of the reported patients had varying degrees of developmental delay, along with shared dysmorphic features and microcephaly, making this a recognizable microdeletion syndrome.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Following the initial report in 2007 by Rajcan-Separovic et al [Rajcan-Separovic et al, 2007], there have been 15 patients reported in the literature with overlapping deletions in this region [Chabchoub et al, 2008;Fannemel and Barøy, 2014;Florisson et al, 2013;Félix and Petrin, 2010;Hancarova et al, 2013;Hucthagowder et al, 2012;Liang et al, 2009;Peter et al, 2014;Piccione et al, 2012;Prontera et al, 2011;de Leeuw et al, 2008], in addition to reports from public databases such as DECIPHER and ISCA [Firth et al, 2009;Miller et al, 2010] and other large studies assessing developmental delay and copy number variants [Cooper et al, 2011;Kaminsky et al, 2011]. All of the reported patients had varying degrees of developmental delay, along with shared dysmorphic features and microcephaly, making this a recognizable microdeletion syndrome.…”
Section: Introductionmentioning
confidence: 97%
“…All of the reported patients had varying degrees of developmental delay, along with shared dysmorphic features and microcephaly, making this a recognizable microdeletion syndrome. Brain imaging findings in these patients suggest the 2p15-16.1 region contains important genes for brain development [Florisson et al, 2013;Hucthagowder et al, 2012;Piccione et al, 2012;Rajcan-Separovic et al, 2007]. Some of the reports of patients with 2p15-16.1 deletion have suggested narrowing the critical region of the neurodevelopmental phenotype to 4 genes; BCL11A, PAPOLG, REL and PEX13 [Hancarova et al, 2013;Liang et al, 2009;Piccione et al, 2012;de Leeuw et al, 2008].…”
Section: Introductionmentioning
confidence: 97%
“…In addition, BCL11A is included in most CNVs reported as the 2p15‐p16.1 microdeletion syndrome (OMIM #612513), characterized by developmental delay, intellectual disability, hypotonia, poor verbal skills, craniofacial and skeletal features, digital anomalies, and fetal hemoglobin persistence (Basak et al, 2015; Funnell et al, 2015). When described, patients with 2p15p16 microdeletion encompassing BCL11A show delayed receptive and expressive language skills (Hancarova et al, 2013; Piccione et al, 2012; Rajcan‐Separovic et al, 2007), language delay (Balci, Sawyer, Davila, Humphreys, & Dyment, 2015; Felix, Petrin, Sanseverino, & Murray, 2010), language restricted to a few single words and signing (Florisson et al, 2013), or absence of language (Florisson et al, 2013; Hucthagowder et al, 2012). Apart from Peter, Matsushita, Oda, and Raskind, (2014), who described a 200 kb 2p15p16.1 deletion encompassing the entire BCL11A gene (plus 50 kb of non‐coding sequence but no other known coding or non‐coding gene) in a patient with mild intellectual disability, childhood apraxia of speech, dysarthria, and oral and motor dyspraxia, language anomalies have not been extensively studied in patients with mutations or microdeletions affecting BCL11A .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8], and the existence of nonoverlapping copy number variants (CNVs) within the 2p15p16.1 deletion region complicate efforts to delineate a common critical region for the syndrome. In addition, some studies suggested that The 2p15p16.1 microdeletion syndrome has a core phenotype consisting of intellectual disability, microcephaly, hypotonia, delayed growth, common craniofacial features, and digital anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…regulatory elements (enhancers) in the region could also play a role (7). Nevertheless, several deletions involving individual genes or smaller numbers of genes were reported (2)(3)(4)(5)(8)(9)(10) XPO1 (also known as CRM1) is a nuclear export receptor that exports approximately 200 different cargo molecules (e.g., proteins, rRNA, small nuclear RNA [snRNA], miR, and specific mRNAs) from the nucleus to the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%